(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
The research aims to study the impact of implementing risk management systems on the performance of the Central Bank of Iraq in three aspects: financial performance, operational performance, and resilience and stability. Materials and Methods A sample of 150 employees was drawn, and a survey was conducted to gather the required information. Data analysis was performed using the statistical software SPSS 25, employing statistical methods such as mean, standard deviation, correlation coefficient, and simple linear regression. Result The results of the investment often appear in search engines and in the ranking of items present in the variables (risk management systems – performance). If you log in at the beginning of the fiscal year, start the operating day and end the time for flexibility and design. The developmental dimension revealed the missing results of the research on the existence of an impact of the trading system on operations in the financial market... The Iranian Central Bank, there is an impact of delivery system applications on the financial situation of the Central Bank of Iraq. It affects the application systems in the operations of the Iraqi Central Bank’s operating system, impacting the systems in the operations, flexibility, and stability of the Central Bank of Iraq. Conclusion: The research results showed that the respondents agreed to a high degree on the paragraphs of each of the variables (risk management systems - performance), achieving the financial performance dimension first, then the operational performance dimension, and finally the flexibility and stability dimension.